What is Unilateralism in International Taxation?. (2020) - Cui, Wei
Abstract : The Organisation for Economic Co-Operation and Development (OECD) recently emerged as the site of unprecedented, multilateral, and seemingly high-stakes negotiations about the future of international business income taxation. Judging by the political resources deployed in these negotiations, international tax has entered unchartered territory. Ruth Mason offers a timely and balanced portrayal of the OECD process so far. But explanations of this process remain eminently contestable. On the one hand, international institutions that address externalities from uncoordinated actions and produce mutual benefits for participating nations can be highly stable. On the other hand, the OECD has struggled, whether in its Base Erosion and Profit Shifting (BEPS) and post-BEPS initiatives or during the pre-BEPS era, to articulate the goals for which international coordination in taxation is needed. By many accounts, recent discussions at the OECD are motivated mainly by the desire to stop foreign imposition of taxes on U.S. companies, or, as the other side of the same coin, to avert the wrath of the single hegemonic power in international tax. What is the best characterization of this conflict? I believe that understanding the underlying subject matter for international coordination, as opposed to merely the institutions that might facilitate such coordination, is required for identifying the coming transformation of international tax.